2022
DOI: 10.3389/fimmu.2022.996134
|View full text |Cite
|
Sign up to set email alerts
|

Early immunological responses to the mRNA SARS-CoV-2 vaccine in patients with neuromuscular disorders

Abstract: BackgroundsIntramuscular injection of the SARS-CoV-2 vaccine has raised concerns about its use in patients with neuromuscular disorders (NMDs). We evaluated the response of patients with NMDs to the BNT162b2 vaccine.MethodsHealthy subjects, patients with spinal muscular atrophy (SMA), and patients with Duchenne muscular dystrophy (DMD) were included. All participants received two BNT162b2 doses. SARS-CoV-2 antibody titers at baseline and 2 weeks after each vaccination were compared between groups. Residual mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Antibody responses were robust, an observation which was consistent with adolescent and adult patients with NMDs and myasthenia gravis who were able to generate antibody responses against WT. (20,21,33) It is reassuring that even for pediatric patients with NMDs and on corticosteroids, all patients had successful seroconversion after at least two doses of BNT162b2 or CoronaVac, which was also observed in adolescent and adult patients who received BNT162b2. (20,33) Additionally, there were no apparent interactions between the COVID-19 vaccines and treatments for NMDs, and our cohort of patients did not encounter NMD-related complications or hospitalization.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Antibody responses were robust, an observation which was consistent with adolescent and adult patients with NMDs and myasthenia gravis who were able to generate antibody responses against WT. (20,21,33) It is reassuring that even for pediatric patients with NMDs and on corticosteroids, all patients had successful seroconversion after at least two doses of BNT162b2 or CoronaVac, which was also observed in adolescent and adult patients who received BNT162b2. (20,33) Additionally, there were no apparent interactions between the COVID-19 vaccines and treatments for NMDs, and our cohort of patients did not encounter NMD-related complications or hospitalization.…”
Section: Resultsmentioning
confidence: 89%
“…There were similar profiles of ARs between pediatric patients with NMDs, our healthy cohort, as well as adolescents and adults with NMDs and multiple sclerosis who received two doses of BNT162b2 or mRNA-1273. (20,27,32,33) This is also the first study to demonstrate the inactivated whole-virus COVID-19 vaccine, CoronaVac, is immunogenic in pediatric patients with NMDs. Antibody responses were robust, an observation which was consistent with adolescent and adult patients with NMDs and myasthenia gravis who were able to generate antibody responses against WT.…”
Section: Resultsmentioning
confidence: 94%
“…We speculate that disease types in MDs may be important contributing factors in predicting antibody response; therefore, further studies will lead to better management of vaccination in MDs. Fourth, previous studies have also showed the immunogenicity associated with SARS-CoV-2 vaccination in patients with MDs using only an intramuscular mRNA vaccine (7,8), but not other SARS-CoV-2 vaccines including protein subunit vaccines and viral vector-based vaccines. In addition, we speculate that a 3rd primary dose, with a higher dose, shorter intervals between vaccines such as 3 months, or an altered delivery method, such as nasal spray or aerosol inhalation, might help to improve vaccine responses in patients with MDs.…”
Section: Limitations In Our Studymentioning
confidence: 96%
“…and Iwayama et al. reported that intramuscular mRNA immunization resulted in a strong IgG antibody response in patients with advanced MDs ( 7 , 8 ). However, there are limited reports on the effect of SARS-CoV-2 vaccines on MDs, in particular for long periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation